Single-pill combination of indapamide and perindopril: potential of practical application - A. M. Kochergina; V. V. Kashtalap (Российский кардиологический журнал, 2024)
The effectiveness of blood pressure control can be increased with the use of single-pill combinations. When choosing an agent, the evidence of its components should be focused. The selection criteria are not only the direct effects of reducing blood pressure, but also organ protection and the impact on prognosis. Perindopril and indapamide have many years of experience in use in a wide range of patients and are used with the same effectiveness in the treatment of hypertension in young and elderly patients, in normal-weight and obese people, as tools for the primary prevention of myocardial infarction and stroke, and also as a way to prevent recurrent events.The article provides data on the advantages of perindopril and indapamide, the potential of its single-pill combination, the pleiotropic and organ protective properties of this drug. We systematized results of related studies and reflected the main conclusions. Attention is paid to the latest data on the long-term effect of indapamide therapy on the risk of cardiovascular events.